Closed-loop for type 1 diabetes – an introduction and appraisal for the generalist. Issue 1 (December 2017) - Bally, Lia; Thabit, Hood; Hovorka, Roman
Abstract Background Rapid progress over the past decade has been made with the development of the 'Artificial Pancreas', also known as the closed-loop system, which emulates the feedback glucose-responsive functionality of the pancreatic beta cell. The recent FDA approval of the first hybrid closed-loop system makes the Artificial Pancreas a realistic therapeutic option for people with type 1 diabetes. In anticipation of its advent into clinical care, we provide a primer and appraisal of this novel therapeutic approach in type 1 diabetes for healthcare professionals and non-specialists in the field. Discussion Randomised clinical studies in outpatient and home settings have shown improved glycaemic outcomes, reduced risk of hypoglycaemia and positive user attitudes. User input and interaction with existing closed-loop systems, however, are still required. Therefore, management of user expectations, as well as training and support by healthcare providers are key to ensure optimal uptake, satisfaction and acceptance of the technology. An overview of closed-loop technology and its clinical implications are discussed, complemented by our extensive hands-on experience with closed-loop system use during free daily living. Conclusions The introduction of the artificial pancreas into clinical practice represents a milestone towards the goal of improving the care of people with type 1 diabetes. There remains a need to understand the impact of user interaction with the technology, and its implication on current diabetes management and care.